Does corporate governance and profitability effect on corporate social responsibility disclosure? - Suryandari, Ni Nyoman Ayu; Susandya, Anak Agung Putu Gede Bagus Arie (Jurnal Ekonomi Modernisasi, 2023)
Trust has a role in establishing successful business relationships, companies must be able to meet the needs of stakeholders. So that corporate governance mechanisms are needed. The CSR disclosure is a form of corporate responsibility to the community and the environmental aspect. Corporate governance in this study is examined in four separate variables, namely the tenure of directors, board size, independent commissioners, and managerial ownership. This study also analyzes the effect the profitability in increasing CSR disclosure level. The sample is 54 observation collected from companies listed on the IDX using the purposive sampling method. Multiple linear regression analysis is used. The results prove that board size, independent commissioners and profitability are able to increase the company's motivation to disclose CSR. While the tenure of directors and managerial ownership are not able to motivate in disclosing CSR. For further research, is expected to examine the characteristics of audit committees, institutional ownership and the number of audit committee meetings.